Effects of bioactive plant extracts on immune-related gene expression of common carp (Cyprinus carpio) - Csernus, Brigitta; Bíró, Sándor; Stündl, László; Remenyik, Judit; Bai, Péter; Fehér, Milán; Minya, Dániel; Czeglédi, Levente (Acta Agraria Debreceniensis, 2020)
In recent years, intensive fish farming has led to an outbreak of several diseases, and the health status of fish can affect the economy of aquaculture. Since fish health and intestinal health are in correlation, it may also have an impact on immunity. Accordingly, many natural feed additives are being used to improve immune functions. In our study, carotenoids, oligosaccharides, and anthocyanins were applied at 1 m/m% in feed to investigate their effects on cytokines, such as interleukin-1β (IL-1β), interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α), and interferon regulatory factor-1 (IRF-1) in spleen and mid-intestine of 6 months old carp. Gene expression analysis was carried out to examine IL-1β, IL-8, TNF-α, and IRF-1 mRNA levels in fish spleen and mid-intestine. The gene expression level of pro-inflammatory IL-1β decreased in the mid-intestine of carotenoid-fed carp compared to anthocyanin supplemented group, but the effects of the bioactive plant extracts were not observed on the examined cytokines compared to control fish.